2017
DOI: 10.1002/aur.1780
|View full text |Cite
|
Sign up to set email alerts
|

Identification of likely associations between cerebral folate deficiency and complex genetic‐ and metabolic pathogenesis of autism spectrum disorders by utilization of a pilot interaction modeling approach

Abstract: Recently, cerebral folate deficiency (CFD) was suggested to be involved in the pathogenesis of autism spectrum disorders (ASD). However, the exact role of folate metabolism in the pathogenesis of ASD, identification of underlying pathogenic mechanisms and impaired metabolic pathways remain unexplained. The aim of our study was to develop and test a novel, unbiased, bioinformatics approach in order to identify links between ASD and disturbed cerebral metabolism by focusing on abnormal folate metabolism, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 80 publications
(105 reference statements)
0
10
0
Order By: Relevance
“…Folate is essential for mitochondrial function [25,65], raising the possibility that insufficiency of folate could account for mitochondrial abnormalities. Others have recently suggested that folate abnormalities and ASD may be connected through other metabolic pathways that are commonly abnormal to both such as serine, lysine and/or purine metabolism [66]. We have recently demonstrated that FRAAs during gestation may play a role in thyroid abnormalities present in children with ASD [67].…”
Section: Future Perspectivementioning
confidence: 78%
“…Folate is essential for mitochondrial function [25,65], raising the possibility that insufficiency of folate could account for mitochondrial abnormalities. Others have recently suggested that folate abnormalities and ASD may be connected through other metabolic pathways that are commonly abnormal to both such as serine, lysine and/or purine metabolism [66]. We have recently demonstrated that FRAAs during gestation may play a role in thyroid abnormalities present in children with ASD [67].…”
Section: Future Perspectivementioning
confidence: 78%
“…As a one-carbon donor, folate is essential for numerous metabolic biochemical processes. Many studies showed the association between genetic and abnormalities of folic acid and the pathogenesis of ASD ( 51 56 ). In addition, in our study, there was a negative association between folate and severity of ASD symptom.…”
Section: Discussionmentioning
confidence: 99%
“…184 Cerebral folate deficiency, together with folate receptors autoantibodies, have also been reported to play a pathological role in cases of ASD. 185 Healthcare professionals should have awareness of and screen for metabolic and/or mitochondrial dysfunction as these physical comorbidities can potentially contribute to ASD severity.…”
Section: Seizure Disorders and Epilepsy In Asdmentioning
confidence: 99%